Chemical synthesis and biological activity of novel brominated 7-deazaadenosine-3′, 5′-cyclic monophosphate derivatives. Issue 8 (15th April 2019) - Lelle, Marco; Otte, Maik; Thon, Susanne; Bertinetti, Daniela; Herberg, Friedrich W.; Benndorf, Klaus
Graphical abstract: Abstract: Synthetic derivatives of cyclic adenosine monophosphate, such as halogenated or other more hydrophobic analogs, are widely used compounds, to investigate diverse signal transduction pathways of eukaryotic cells. This inspired us to develop cyclic nucleotides, which exhibit chemical structures composed of brominated 7-deazaadenines and the phosphorylated ribosugar. The synthesized 8-bromo- and 7-bromo-7-deazaadenosine-3′, 5′-cyclic monophosphates rank among the most potent activators of cyclic nucleotide-regulated ion channels as well as cAMP-dependent protein kinase. Moreover, these substances bind tightly to exchange proteins directly activated by cAMP.